Motherhood as Performance: (Re)Negotiations of Motherhood in Contemporary German Literature - Alexandra Merley Hill (Studies in 20th & 21st Century Literature, 2011)
While the birth rate in Europe remains low, the role of motherhood is hotly debated in Germany—particularly in conjunction with the revival of feminism in that country. In the context of these debates, this article analyzes the representation of mothers in three contemporary novels by German authors: Himmelskörper (2003) by Tanja Dückers, Die Gunnar-Lennefsen-Expedition (1998) by Kathrin Schmidt, and Die Mittagsfrau (2007) by Julia Franck. All three books are informed by a feminist perspective, but only Die Mittagsfrau offers a new way of thinking about motherhood; while Dückers and Schmidt ultimately do not depart from the connection between motherhood and the female body, Franck represents motherhood as a performative identity, in the sense of Judith Butler’s theory of performative gender. “Maternal drag,” as articulated in this article, theorizes the identity mother as a performative one, illuminating expectations of that role and thereby opening it up to possible reconfiguration.
Keywords: birth rate; role of motherhood; motherhood; feminism; representation of mothers; Germany; Himmelskörper; Tanja Dückers; Die Gunnar-Lennefsen-Expedition; Kathrin Schmidt; Die Mittagsfrau; Julia Franck; feminist literature; feminist perspective; female body; performative identity; Judith Butler; mother; identity